Upaya Meningkatkan Minat dan Hasil Belajar Matematika melalui Metode Pembelajaran Examples Non Examples Siswa Kelas VII-B MTs N Bantul Tahun Pelajaran 2014/2015 - Wening Tri Sulistyawati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
This research aims to develop learning process in the classroom, to increase interest in and the results of learning math grade VII B MTs Country I Bantul, especially at the subject of flat areas of rectangle using learning methods examples non examples. This research is a research action class that is intended to solve the existing problems in the classroom by utilizing real action then happens and do a reflection against the results of the action. Research progress of pre cycle, cycle 1 and cycle 2, each cycle is divided into three times. Each cycle consists of three phases, namely, planning, execution and observation, reflection. The results showed that the implementation of learning by using learning methods examples non examples in class 1 MTsN VII B Bantul can increase interest and learning results. It can be seen from the learning interest of students in classes VII B at low cycle 31.3% pre and the cycle is currently 43.7%, cycle 1 are 50% and 47% Higher, cycle-cycle II were 44% and 50% higher cycle. While the observations on interest in learning of students from 75% to 85% in cycle II and the results of study students complete 50% to 72% complete on cycle II.